Det postapokalyptiske moderskab: Megan Hunters The End We Start From - Marcussen, Marlene Karlsson (Passage - Tidsskrift for litteratur og kritik, 2019)
The article investigates a new type of narrative, where motherhood and catastrophe are interwoven. This inquiry questions how Megan Hunter presents the mother as heroine of a new type of feminist science fiction and how she uses a postapocalyptic frame to depict motherhood in crisis by showing how language falls short of fathoming experiences – both of birth and flood – beyond human understanding. Hunter’s novel succeeds in intertwining the events of motherhood and apocalypse, thus showing how both lend their language and experience to each other.